Pemberdayaan gerakan kesejahteraan keluarga untuk pencegahan kekerasan dalam rumah tangga di Desa Campaka Purwakarta - Diah Zaleha Wyandini; Gemala Nurendah; Sri Maslihah; Muhammad Ariez Musthofa; Ita Juwitaningrum; Engkos Kosasih (Universitas Pendidikan Indonesia, 2026)
Community service in Campaka Village, Purwakarta Regency, focused on empowering cadres of the Family Empowerment and Welfare Movement Team (Tim Penggerak Pemberdayaan dan Kesejahteraan Keluarga/TP PKK) to prevent domestic violence, strengthen family resilience, and protect children. Domestic violence remains a social issue that can be influenced by a lack of knowledge, fear, economic dependence, power relations, a culture of silence, and limited access to perceived safe support. The method used was a quasi-experimental one-group pretest-posttest design through a community-based psychoeducational intervention. The activity involved 40 TP PKK cadres, with 33 participants completing the pre-test and post-test questionnaires. The activity covered an introduction to domestic violence, family resilience, and child-friendly villages. The results showed an increase in cadre knowledge, as indicated by a higher percentage of cadres in the high category. This activity also included counseling for children and families who are victims of sexual abuse. For future village programs and community service teams, it is recommended to continue implementing ongoing education, mentoring cadres, and strengthening community-based referral networks.